Pembinaan SDM Kelompok Remaja dalam Pelestarian Kesenian Tradisional Randai Minangkabau - Syamsir Syamsir; Jumiati Jumiati; Ideal Putra (Faculty of Social Science, Universitas Negeri Padang, 2022)
This study (article) was summarized based on experiences of Community Service program among younger generation in Padang Laweh Malalo Village at Tanah Datar Regency. This program was intended to increase the understanding and awareness the younger generation to the importance of preserving the traditional arts of randai as one of the cultural heritages and at the same time the potential and tourist attraction that has been neglected all this time. This study was inspired by various conditions that indicated the lack of interest, awareness, and skills of the younger generation in preserving this randai art, while on the other hand traditional randai art can be used as an attraction and is a potential for cultural tourism that can be packaged and adapted to the current context. Based on this condition, various coaching, training and management programs would be needed to improve the abilities and skills of partner groups, especially the youth group who were members of the